Elevated Foxp3+ double-negative T cells are associated with disease progression during HIV infection - Zhang, Leidan; Wei, Yuqing; Wang, Di; Du, Juan; Wang, Xinyue; Li, Bei; Jiang, Meiqing; Zhang, Mengyuan; Chen, Na; Deng, Meiju; Song, Chuan; Chen, Danying; et al. (Frontiers in Immunology, 2022)
Persistent immune activation, which occurs during the whole course of HIV infection, plays a pivotal role in CD4+ T cells depletion and AIDS progression. Furthermore, immune activation is a key factor that leads to impaired immune reconstitution after long-term effective antiretroviral therapy (ART), and is even responsible for the increased risk of developing non-AIDS co-morbidities. Therefore, it’s imperative to identify an effective intervention targeting HIV-associated immune activation to improve disease management. Double negative T cells (DNT) were reported to provide immunosuppression during HIV infection, but the related mechanisms remained puzzled. Foxp3 endows Tregs with potent suppressive function to maintain immune homeostasis. However, whether DNT cells expressed Foxp3 and the accurate function of these cells urgently needed to be investigated. Here, we found that Foxp3+ DNT cells accumulated in untreated people living with HIV (PLWH) with CD4+ T cell count less than 200 cells/µl. Moreover, the frequency of Foxp3+ DNT cells was negatively correlated with CD4+ T cell count and CD4/CD8 ratio, and positively correlated with immune activation and systemic inflammation in PLWH. Of note, Foxp3+ DNT cells might exert suppressive regulation by increased expression of CD39, CD25, or vigorous proliferation (high levels of GITR and Ki-67) in ART-naive PLWH. Our study underlined the importance of Foxp3+ DNT cells in the HIV disease progression, and shed light on a promising clinical intervention for the control of immune activation during HIV infection.